Associations of Chronic Kidney Disease With Dementia Before and After TIA and Stroke: Population-Based Cohort Study. (15th February 2022) - Kelly, Dearbhla M.; Pendlebury, Sarah T.; Rothwell, Peter M.
Abstract : Background and Objectives: Individuals with chronic kidney disease (CKD) appear to be at increased risk of cognitive impairment, with both vascular and neurodegenerative mechanisms postulated. To explore the vascular hypothesis, we studied the association between CKD and dementia before and after TIA and stroke. Methods: In a prospective, population-based cohort study of TIA and stroke (Oxford Vascular Study; 2002–2012), pre-event and new postevent dementia were ascertained through direct patient assessment and follow-up for 5 years, supplemented by review of hospital/primary care records. Associations between pre-event dementia and CKD (defined as an estimated glomerular filtration rate [eGFR] <60 mL/min/1.73 m 2 ) were examined using logistic regression and between postevent dementia and CKD using Cox and competing risk regression models, adjusted for age, sex, education, stroke severity, prior stroke, white matter disease, diabetes mellitus, and dysphasia. Results: Among 2, 305 patients with TIA/stroke (median [interquartile range] age, 77 [67–84] years, 1, 133 [49%] male, 688 [30%] TIA), 1, 174 (50.9%) had CKD. CKD was associated with both pre-event (odds ratio [OR] 2.04 [95% confidence interval (CI) 1.52–2.72]; p < 0.001) and postevent dementia (hazard ratio [HR] 2.01 [95% CI 1.65–2.44]; p < 0.001), but these associations attenuated after adjustment for covariates (OR 0.92 [0.65–1.31]; p = 0.65 and HR 1.09 [0.85–1.39]; p = 0.50). The results were similar when a competing risk model was used (subdistribution HR [SHR] 1.74 [1.43–2.12]; p < 0.001, attenuating to 1.01 [0.78–1.33]; p = 0.92 with adjustment). CKD was more strongly associated with late (>1 year) postevent dementia (SHR 2.32 [1.70–3.17]; p < 0.001), particularly after TIA and minor stroke (SHR 3.08 [2.05–4.64]; p < 0.001), but not significantly so after adjustment (SHR 1.53 [0.90–2.60]; p = 0.12). Discussion: In patients with TIA and stroke, CKD was not independently associated with either pre- or postevent dementia, suggesting that renal-specific mechanisms are unlikely to play an important role in aetiology.